Exploring the Relationship Between Social Media, Collaborative Learning and Learners’ Satisfaction - Lam, Jing Hin; Ma, Will Wai-Kit (Blended Learning: Aligning Theory with Practices, 2016)
Social Media Platforms have become more and more popular and important in daily life. Then, it may be a factor that affecting students’ learning satisfaction while it may be an enhancing tool or disturbance. So this study is going to find out whether social media enhance students’ learning satisfaction or not by the factors of social media using behavior, purpose of using social media and collaborative learning. The research question was “Would social media enhance students’ learning satisfaction?” This study administered a survey questionnaire to 204 university students. Results found that social media behavior (β = .128, p < .05) and academic purpose (β = .667, p < .001) had direct, significant and positive relationship with collaborative learning (β = .763, p < .001) which had a significant and direct positive effect on students’ learning satisfaction (R2 = .582). Implications of the factors in predicting satisfaction were discussed.